2007
DOI: 10.1148/radiol.2441061122
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography: False-Negative Interpretations

Abstract: The major contributor to error at CT colonography was observer perceptual error, while observer measurement error played a smaller role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…known that most polyps missed at unassisted reading are actually visible on the CT scan when studies are reviewed in retrospect by experienced readers (28,29). In this trial we have shown that observer error is reduced by the addition of CAD.…”
mentioning
confidence: 63%
“…known that most polyps missed at unassisted reading are actually visible on the CT scan when studies are reviewed in retrospect by experienced readers (28,29). In this trial we have shown that observer error is reduced by the addition of CAD.…”
mentioning
confidence: 63%
“…22 The research value of image databases acquired during clinical studies has been realized in other anatomic sites as well, such as CT colonography. 23,24 The development of CAD methods for lung nodule detection, classification, and quantitative assessment can be facilitated and stimulated through the creation of a wellcharacterized repository of thoracic CT scans. A true reference database, however, would provide an even greater benefit to investigators but would require an even greater commitment of time and resources to create the standards and infrastructure required to capture metadata, such as image annotations and pathologic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Current challenges of CT colonography include variable sensitivity and specificity among readers and long learning curves for new readers (similar to mammography). Most reader errors are avoidable and result from errors of detection (12)(13)(14). Computer-aided detection (CAD) is designed to decrease errors of detection by finding and displaying possible polyps to be evaluated by the reader (15)(16)(17)(18).…”
Section: Frequency Of Cad False-positive Resultsmentioning
confidence: 99%